Evaluación del suero sanguíneo enriquecido con ozono (O3) para la cicatrización de heridas caninas - Anguieta Villa, Jonathan David (2023)
Evaluation of blood serum enriched with ozone (O3) for the healing of canine wounds, the objectives that were established are: to determine the efficiency of ozone (O3) in the healing process of canine wounds, to establish the healing time in each of the patients and analyze the inflammatory processes of the surgical patients submitted to the investigation, blood serum enriched with ozone (O3) and 30 female canines with ovariohysterectomy (OVH) wounds were used, the method was investigative and practical, the factor under study refers to The healing process in canine wounds using ozone-enriched blood serum (O3), began with a blood sample from patients with wounds, then the sample was centrifuged to obtain the blood serum, ozone was added to it (O3) and enriched it; This process was carried out in the respective machine that generates ozone (O3) and finally it was placed in each of the wounds of the patients so that it began with the function in terms of healing, the 30 patients were subjected to the first application of blood serum enriched with ozone (O3), on the other hand, at the second check-up and second application only 23 received the treatment because 7 of them presented infected wounds that had to be corrected, for this reason we proceeded to divide them by phases, in the third application the 23 were accessible while the remaining 7 had their applications in the second phase.